Smart parking system using parking space tracking module and GIS / Mohd Firdaus Abdul Rahman - Abdul Rahman, Mohd Firdaus (2017)
Frustration of finding an available parking space is still a common issue in big cities, especially during weekend and peak hours. Although various of smart parking system has been introduced since 1970's, this issues seem still not solve. The aim of this research is to study the different type of smart parking system and vehicle detection technologies that can be use in existing smart parking system. In order to help patrons on easy finding available parking space, this research will integrate the selected vehicle detection technologies into existing parking system. Herein, this research will use video image processing with interest point detection Scale Invariant Feature Transform (SIFT) as occupancy detection module and Geographic Information System (GIS). goNpark will be use to guide patron to find the available parking space easily and accurately. goNpark will provide real-time visualization of parking situation of patrons destination.